2018
DOI: 10.1111/cch.12614
|View full text |Cite
|
Sign up to set email alerts
|

Children with specific language impairment are more likely to reach motor milestones late

Abstract: More children with SLI are late in reaching motor milestones than children without SLI. This means that it is debatable whether SLI can be regarded as a "specific" impairment, which is not associated with other developmental problems. A broader developmental assessment is therefore indicated when diagnosing SLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
2
3
0
2
Order By: Relevance
“…we observed that children with the developmental disorders have de cits in all domains assessed by the GDDS compared to normally developing children (indicated by high ratings of inadequate development as shown in Table 3). This observation is in accordance with the literature in which developmental disabilities, which are mainly manifested by cognitive, social, gross motor, and ne motor skills are reported for children with DLD [35,36,37] and ASD [38,39,40,41]. Moreover, we observed a negative low-to-moderate correlation between all domains of the GDDS (i.e., adaptive behavior, gross motor skills, ne motor skills, language abilities, and personal-social behavior) and severity of the autism spectrum disorder (operationalized by CARS score) in children with ASD implying a type of "doseresponse" relationship between disease severity and de cits in functional abilities.…”
Section: Discussionsupporting
confidence: 93%
“…we observed that children with the developmental disorders have de cits in all domains assessed by the GDDS compared to normally developing children (indicated by high ratings of inadequate development as shown in Table 3). This observation is in accordance with the literature in which developmental disabilities, which are mainly manifested by cognitive, social, gross motor, and ne motor skills are reported for children with DLD [35,36,37] and ASD [38,39,40,41]. Moreover, we observed a negative low-to-moderate correlation between all domains of the GDDS (i.e., adaptive behavior, gross motor skills, ne motor skills, language abilities, and personal-social behavior) and severity of the autism spectrum disorder (operationalized by CARS score) in children with ASD implying a type of "doseresponse" relationship between disease severity and de cits in functional abilities.…”
Section: Discussionsupporting
confidence: 93%
“…62,63 Children with DLD systematically showed weaker performance on tests of gross and fine motor skills compared with their peers, 64 were impaired at tasks that required for them to synchronize tapping to a beat 65 ; and showed delayed motor development. 66 These observations were consistent with findings that developmental coordination disorder, which affects fine motor skills, was often comorbid with DLD. 5,[67][68][69] The other 2 sets of comorbidities that were associated with DLD were atopic disorders and sleep disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, factors such as motor functioning or sensory processing may play a role in explaining the observed variation in the domain of repetitive and restricted behaviors ( Berry et al, 2018 ). Impairments in these domains have been reported in children with DLD ( Diepeveen et al, 2017 ) and in children with 22q11DS ( Van Aken et al, 2009 ). Future studies would need to shed light to what extent the influence of such factors is on the development of ASD-related behaviors, in these groups of children.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%